Reading Disability in a Time of Posthuman Work: Speed and Embodiment in Joshua Ferris' The Unnamed and Michael Faber's Under the Skin - Stuart Murray (Disability Studies Quarterly, 2017)
This article analyzes a contemporary posthuman culture of work through a critical disability optic and, in particular, examines the disability aesthetics employed by Ferris and Faber in their novels. It opens with an outline of how contemporary post-industrial work cultures fixate on notions of speed and efficiency, and then reads the ideas of 'humanity', embodiment and power that result from this, before situating the difference of disability as a critique of such focus on immediacy and productivity. Ferris' and Faber's novels are read in terms of their analysis of disability and work, exploring how each creates complex ideas of embodiment, time and subjectivity from their very different contexts (the corporate world of the Manhattan legal profession in The Unnamed and an isolated alien/posthuman work environment of food production in Under the Skin). While offering a critique of the posthuman as it is figured in neo-liberal conceptions of work, the article concludes by suggesting the productive possibilities of aligning a critical posthumanist anti-humanism with contemporary disability theory in further understanding representations of work and disability.
Keywords: Disability; Posthuman; Work; Contemporary Fiction